Intracrine Dynamics of Luminal Breast Cancer: Correlating Intratumoral Estradiol with Estrogen Receptor Alpha Overexpression in an Advanced-Stage Cohort - Erdiansyah Reza Lesmana; Widyanti Soewoto; Brian Wasita (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2026)
Background: In postmenopausal breast cancer, systemic serum estradiol levels often fail to reflect the biologically active concentrations within the tumor microenvironment, a phenomenon known as intracrineology. While the roles of estrogen receptor alpha (ERα) and beta (ERβ) are well-characterized, the specific relationship between local ligand concentration and receptor expression in advanced-stage malignancies remains under-investigated. This study investigates the correlation between intratumoral estradiol (E2) concentration and the expression of ER isoforms in Luminal A and Luminal B subtypes. Methods: A retrospective cross-sectional study was conducted on 56 tissue samples (38 Luminal A, 18 Luminal B) from patients at Dr. Moewardi Regional General Hospital, Indonesia. Pre-analytical variables were strictly controlled, ensuring cold ischemia time was less than one hour. Expressions of E2, ERα, and ERβ were quantified using immunohistochemistry and assessed via H-Scores. Due to non-normal data distribution, associations were analyzed using Spearman’s Rho and Generalized Linear Models (GLM) with a Gamma distribution and log-link function, coupled with bootstrapping to generate robust confidence intervals. Results: The cohort was characterized by advanced disease, with 85.7% of patients presenting with Stage III or IV breast cancer. Luminal A tumors exhibited significantly higher mean intratumoral E2 (91.58 versus 56.67; p = 0.038) and ERα expression (122.23 versus 109.72; p = 0.045) compared to Luminal B. A significant positive correlation was observed between tissue E2 and ERα (Rho = 0.347; p = 0.009). GLM analysis confirmed E2 as a significant predictor of ERα expression (p = 0.015), independent of age and stage. No significant correlation was found between E2 and ERβ (p = 0.113). Conclusion: Intratumoral estradiol is a significant positive correlate of ERα expression in luminal breast cancer, supporting the existence of a ligand-driven autocrine maintenance loop even in advanced stages. The lack of correlation with ERβ suggests divergent regulatory mechanisms. These findings reinforce the rationale for therapies targeting local aromatase activity.